Protective Efficacy of Langsat (Lansium domesticum) Peel Extract Lotion Against Aedes Mosquito Bites - Novarianti, Novarianti; Saharudin, Saharudin; Sunuh, Herlina Susanto (Banua: Jurnal Kesehatan Lingkungan, 2025)
Background: Aedes mosquitoes are the main vectors of dengue fever (DF), which remains a public health problem in Indonesia. Excessive use of chemical repellents can cause adverse effects on humans and the environment, so safe and effective natural alternatives are needed. This study aims to determine the protective power of langsat peel extract (Lansium domesticum) as a repellent against Aedes sp. mosquitoes. Method: Experimental with a post-test only with a control group design. The variations in extract concentration used were 15%, 20%, 25%, and 30%, with five repetitions. The parameters observed were the number of mosquitoes that landed during six hours of observation every five minutes, and the results were analyzed descriptively and quantitatively using the protection power formula  Result: The results showed that the protective power of langsat peel extract increased with concentration, namely 84% at a concentration of 15% (not protective), 95% at 20% (highly protective), and 100% at 25% and 30% (highly protective). Conclusion: Langsat peel extract with a concentration of ≥20% is effective as a natural repellent against Aedes sp. mosquitoes and has the potential to be developed as an environmentally friendly natural repellent base ingredient